2010
DOI: 10.1039/b925927a
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of structural and charge-transfer barrier properties of n-alkanethiol layers on a polycrystalline copper surface by electrochemical potentiodynamic polarization

Abstract: A method that significantly improves the charge-transfer barrier properties of self-assembled n-alkanethiol films on polycrystalline copper is presented in this paper. Chemically-formed films were further modified electrochemically by repetitive potentiodynamic cycling in ethanolic solutions containing small quantities of n-alkanethiols. The polarization modulation infrared reflection absorption spectra (PM-IRRAS) of the electrochemically-modified thiol films showed an increase in their surface packing density… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 26 publications
0
18
0
Order By: Relevance
“…The dynamic parameters associated with polarization curves, such as the corrosion potential (E corr ) and corrosion current (i corr ), were obtained by extrapolating the linear portions of the anodic and cathodic branches to their intersection [24]; the data are summarized in Table 1. The inhibition efficiency () was calculated using the following equation [25]: where i corr • and i corrí represent the current densities of the bare copper and tailored electrodes, respectively. As evidenced from Fig.…”
Section: Potentiodynamic Polarization Analysismentioning
confidence: 99%
“…The dynamic parameters associated with polarization curves, such as the corrosion potential (E corr ) and corrosion current (i corr ), were obtained by extrapolating the linear portions of the anodic and cathodic branches to their intersection [24]; the data are summarized in Table 1. The inhibition efficiency () was calculated using the following equation [25]: where i corr • and i corrí represent the current densities of the bare copper and tailored electrodes, respectively. As evidenced from Fig.…”
Section: Potentiodynamic Polarization Analysismentioning
confidence: 99%
“…Fourier transform infrared (FT-IR) spectra of pure CA as well as those of modified electrodes such as Hy/Cu, CA/Cu, Hy/CA/Cu 35 were recorded using JASCO 460 plus model spectrometer in the absorption mode with a frequency range between 4000-400 cm -1 . The IR spectra of the coated substrates were recorded after scratching the respective films formed over copper surface.…”
Section: Characterization Of Monolayers By Ft-ir Spectroscopymentioning
confidence: 99%
“…Above this region, a new mixed-kinetics region appeared due to the formation of divalent copper species as a result the current increases steeply was considered as limiting region. [33][34][35] showed that the Hy/CA/Cu electrode not only inhibited the anodic metal dissolution but also suppressed the cathodic oxygen reduction reaction effectively. The dynamic parameters such as corrosion current (i corr ) and corrosion potential (E corr ) were determined by extrapolating the polarization curves and 25 they are summarized in Table 3.…”
Section: Fig 7 and Table 2 323mentioning
confidence: 99%
See 1 more Smart Citation
“…Results evidence that the potential cycling increases the rate of the SAM formation and induces a significant structural changes in the monolayer (7,19). Thioaromatic SAMs on copper were modified by potential cycling in ethanol containing milimolar concentration of 1-dodecanthiol (DT).…”
Section: Introductionmentioning
confidence: 99%